The Direct and Indirect Costs Associated With Overactive Bladder Within a Commercially-Insured Population in the United States. Issue 9 (September 2018) - Durden, Emily; Walker, David; Gray, Stephani; Fowler, Robert; Juneau, Paul; Gooch, Katherine
Abstract : Objective: To quantify the burden associated with overactive bladder (OAB) within a commercially-insured United States (US) population. Methods: Adults with OAB identified from the MarketScan ® databases (2008 to 2013) were propensity score matched 1:1 to non-OAB controls. Per-patient-per-month (PPPM) direct healthcare costs, and indirect costs attributable to workplace absence and short-term disability (STD), were estimated. Results: Adjusted PPPM healthcare costs were higher for OAB patients than matched controls for both direct costs ($3003 vs $1123; P  < 0.0001) and indirect costs due to STD ($114 vs $98; P  < 0.05). There was no difference in the indirect costs due to absence between the OAB cases and controls. Conclusions: The direct healthcare costs of OAB patients are substantial. Additional research is needed to quantify the impact of OAB on workplace productivity. Improved management of OAB symptoms may reduce costs and enhance patient quality of life.